2007
DOI: 10.1021/ci700157b
|View full text |Cite
|
Sign up to set email alerts
|

y-Randomization and Its Variants in QSPR/QSAR

Abstract: y-Randomization is a tool used in validation of QSPR/QSAR models, whereby the performance of the original model in data description (r2) is compared to that of models built for permuted (randomly shuffled) response, based on the original descriptor pool and the original model building procedure. We compared y-randomization and several variants thereof, using original response, permuted response, or random number pseudoresponse and original descriptors or random number pseudodescriptors, in the typical setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
496
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 788 publications
(507 citation statements)
references
References 42 publications
6
496
0
5
Order By: Relevance
“…The proposed model was considered robust if the new models on the set with randomized responses presented signifi cantly lower r 2 and Q 2 than the original model. In addition, as a more critical test, randomized response data were used to run from the beginning the model development procedure (Rücker et al, 2007). Finally, external validation was performed in the fi nal model by splitting the data set into several training and test sets.…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…The proposed model was considered robust if the new models on the set with randomized responses presented signifi cantly lower r 2 and Q 2 than the original model. In addition, as a more critical test, randomized response data were used to run from the beginning the model development procedure (Rücker et al, 2007). Finally, external validation was performed in the fi nal model by splitting the data set into several training and test sets.…”
Section: Multivariate Data Analysismentioning
confidence: 99%
“…Y-randomization test has been widely used to evaluate the robustness of a QSAR model, 28,29 In this work, five random shuffles of the y vector were performed and results were listed in Table 6. Results shown in Table 6 suggested that values of R 2 and Q 2 of these new random models were significant lower than those of our original model.…”
Section: Resultsmentioning
confidence: 99%
“…At first, the statistical parameters of the LOO-CV were checked. According to the obtained results, it is remarked that the internal predictions are good because the variance explained in the prediction by LOO (Q At last, to demonstrate that the model was not the result of a chance in fitting given data, the Y-scrambling procedure was employed, placing the answers (dependent variable) at random, keeping all descriptors (independent variables) in the model, and then, performing whole model building procedure n times again [53]. If the model performance decays dramatically, it is a sign of a lack of chance.…”
Section: Validation Of Qsar Modelmentioning
confidence: 99%